3/2x-6=8+2x

Simple and best practice solution for 3/2x-6=8+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3/2x-6=8+2x equation:



3/2x-6=8+2x
We move all terms to the left:
3/2x-6-(8+2x)=0
Domain of the equation: 2x!=0
x!=0/2
x!=0
x∈R
We add all the numbers together, and all the variables
3/2x-(2x+8)-6=0
We get rid of parentheses
3/2x-2x-8-6=0
We multiply all the terms by the denominator
-2x*2x-8*2x-6*2x+3=0
Wy multiply elements
-4x^2-16x-12x+3=0
We add all the numbers together, and all the variables
-4x^2-28x+3=0
a = -4; b = -28; c = +3;
Δ = b2-4ac
Δ = -282-4·(-4)·3
Δ = 832
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{832}=\sqrt{64*13}=\sqrt{64}*\sqrt{13}=8\sqrt{13}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-28)-8\sqrt{13}}{2*-4}=\frac{28-8\sqrt{13}}{-8} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-28)+8\sqrt{13}}{2*-4}=\frac{28+8\sqrt{13}}{-8} $

See similar equations:

| 3/2x+6=8+2x | | (4x-55)+(x+5)=(7x-130) | | 3/2-6=8+2x | | (8x+5)+(4x-5)=(11x+10) | | 2−2s=4/3​+s+13 | | 16z+16+3=0 | | 9x+3=7(2x-1) | | 3x+4x+2x+x=-1+3 | | 12x+(3x+8)=48 | | 3x+79=0 | | X+2=5(2x-2) | | (a+1)³=64 | | 8x+3x=12+7x | | 6/b=42 | | 9-v=-24 | | 4(5n+1)=-96 | | 4(2)-5y=-12 | | 8x-7-3x=-52 | | -10=18-a/7 | | -7-k=8 | | -5p=730 | | 17+d=4 | | 16x=172 | | (p*5950)-(280150)=30000 | | F(x)=2(3)^x | | Y=-x^2-6x+45 | | 4g+(6+2g)⋅3=4 | | Y=-9x^2+14x+1 | | xX0.15=100 | | 1/6y-1/3=10/12y+1 | | 20/2(5+5)=x | | (16)^7t=10 |

Equations solver categories